Improving Quality of Life Among Latina Intimate Partner Violence Survivors Through Economic Empowerment - Cardenas, Iris (Journal of interpersonal violence, 2022)
This study examined the relationship between (1) quality of life and forms of intimate partner violence (IPV) (i.e., psychological abuse, physical violence, sexual violence, and types of economic abuse), and (2) quality of life and economic empowerment among Latina IPV survivors. The authors used data from the Moving Ahead financial literacy program evaluation (n = 200). Nested random-effects models were conducted. Findings indicated that psychological abuse and economic control were significantly and negatively associated with quality of life. Economic empowerment (i.e., financial knowledge, economic self-efficacy, and economic self-sufficiency) was significantly and positively related to Latinas? quality of life. Financial strain was inversely associated with Latina?s quality of life. These findings highlight the importance of identifying strategies for increasing the overall well-being of Latina IPV survivors. Economic empowerment interventions can be an effective mechanism for improving their quality of life. As such, domestic violence organizations should include economic empowerment as part of the services offered to survivors.